Selecting of statins optimum dosage regimen in patients with acute Q-wave myocardial infarction after thrombolytic therapy - V. D. Syvolap; S. M. Kyselov; A. A. Alferov (Zaporožskij Medicinskij Žurnal)
Cardiovascular diseases is the leading cause of death in the Ukraine in a nowadays. Despite the priority role of angioplasty in the treatment of acute Q-wave myocardial infarction, as demonstrated in recent clinical trials, in our country still actual urgent pharmacological recanalization of infarct-associated artery, that is thrombolytic therapy. However, during thrombolytic therapy in many cases fail to achieve optimal reperfusion of the myocardium, resulting in an active search for factors that increase the effectiveness of thrombolytic therapy, and medications that can improve the flow of Q-wave myocardial infarction. In this context, stabilization of atherosclerotic process is a priority after thrombolytic therapy in patients with acute Q-wave myocardial infarction. Pleotropic effects of statins allowed to justify the early administration of drugs in this group of patients after thrombolytic therapy, but there are some differences as to prescribe the dose that is appropriate in these conditions.